2023
DOI: 10.3390/molecules28052148
|View full text |Cite
|
Sign up to set email alerts
|

Berberine-Based Carbon Quantum Dots Improve Intestinal Barrier Injury and Alleviate Oxidative Stress in C57BL/6 Mice with 5-Fluorouracil-Induced Intestinal Mucositis by Enhancing Gut-Derived Short-Chain Fatty Acids Contents

Abstract: This study aims to evaluate the effect of berberine-based carbon quantum dots (Ber-CDs) on improving 5-fluorouracil (5-FU)-induced intestinal mucositis in C57BL/6 mice, and explored the mechanisms behind this effect. Thirty-two C57BL/6 mice were divided into four groups: normal control (NC), 5-FU-induced intestinal mucositis model (5-FU), 5-FU + Ber-CDs intervention (Ber-CDs), and 5-FU + native berberine intervention (Con-CDs). The Ber-CDs improved body weight loss in 5-FU-induced mice with intestinal mucositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…Nucleotide-binding oligomerization domain-like receptor protein (NLRP) has many subtypes, such as NLRP1, NLRP3, NLRP6, and NLRC4 [ 40 ]. Our findings and those of other researchers show that NLRP3 inflammasome is one of the most studied cytoplasmic inflammasomes, and it plays a key role in the innate immune defense after infection by bacteria, fungi, and viruses, and its overactivation can participate in the occurrence and development of a variety of chronic diseases [ 41 , 42 ]. Studies have shown that the activation of NLRP3 inflammasome in the liver, skeletal muscle, and other tissues can significantly increase the risk of T2DM [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 73%
“…Nucleotide-binding oligomerization domain-like receptor protein (NLRP) has many subtypes, such as NLRP1, NLRP3, NLRP6, and NLRC4 [ 40 ]. Our findings and those of other researchers show that NLRP3 inflammasome is one of the most studied cytoplasmic inflammasomes, and it plays a key role in the innate immune defense after infection by bacteria, fungi, and viruses, and its overactivation can participate in the occurrence and development of a variety of chronic diseases [ 41 , 42 ]. Studies have shown that the activation of NLRP3 inflammasome in the liver, skeletal muscle, and other tissues can significantly increase the risk of T2DM [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 73%